Ginsenoside Rg1 interferes with the progression of diabetic osteoporosis by promoting type H angiogenesis modulating vasculogenic and osteogenic coupling - Chen, Wenhui; Jin, Xinyan; Wang, Ting; Bai, Rui; Shi, Jun; Jiang, Yunxia; Tan, Simin; Wu, Ruijie; Zeng, Shiqi; Zheng, Hongxiang; Jia, Hongyang; Li, Shuanglei (Frontiers in Pharmacology, 2022)
Ginsenoside Rg1 (Rg1) has been demonstrated to have antidiabetic and antiosteoporotic activities. The aim of this study was to investigate the protective effect of Rg1 against diabetic osteoporosis and the underlying mechanism. In vitro, we found that Rg1 increased the number of osteoprogenitors and alleviated high glucose (HG) induced apoptosis of osteoprogenitors by MTT assays and flow cytometry. qRT‒PCR and western blot analysis suggested that Rg1 can also promote the secretion of vascular endothelial growth factor (VEGF) by osteoprogenitors and promote the coupling of osteogenesis and angiogenesis. Rg1 can also promote the proliferation of human umbilical vein endothelial cells (HUVECs) cultured in high glucose, enhance the angiogenic ability of endothelial cells, and activate the Notch pathway to promote endothelial cells to secrete the osteogenesis-related factor Noggin to regulate osteogenesis, providing further feedback coupling of angiogenesis and osteogenesis. Therefore, we speculated that Rg1 may have similar effects on type H vessels. We used the Goto-Kakizaki (GK) rat model to perform immunofluorescence staining analysis on two markers of type H vessels, Endomucin (Emcn) and CD31, and the osteoblast-specific transcription factor Osterix, and found that Rg1 stimulates type H angiogenesis and bone formation. In vivo experiments also demonstrated that Rg1 promotes VEGF secretion, activates the Noggin/Notch pathway, increases the level of coupling between type H vessels and osteogenesis, and improves the bone structure of GK rats. All of these data reveal that Rg1 is a promising candidate drug for treating diabetic osteoporosis as a potentially bioactive molecule that promotes angiogenesis and osteointegration coupling.